Learning Media Innovation to Improve the Ability to Remember Hijaiyah Letters for the Deaf - Lia Apriliani; Imas Diana Aprilia (Journal of ICSAR, 2022)
Deaf people have difficulty in remembering things that are abstract so it is absolutely necessary learning media that can help the subject matter more concrete. The purpose of this study is to prove the effectiveness of Bhilar learning media in improving the ability to remember hijaiyah letters in deaf people. The research uses a quantitative approach to the Single Subject Research (SSR) method of A-B-A design. The subjects of this study were DN (12 years old) and OC (11 years). Based on the results of data processing, the baseline phase level mean 1 (A1) was obtained in the DN subject by 18.43 percent and OC by 15.62 percent. Mean intervention phase level (B) in DN subjects was 67.22 percent  and OC was 58.89 percent. Mean baseline phase level 2 (A2) in DN subjects by 95 percent and OC by 86.87 percent. Then it can be concluded that Bhilar learning media proved effective in improving the ability to remember hijaiyah letters because Bhilar learning media uses visual imagery that forms mental images of information.